2010
DOI: 10.4137/cmo.s6413
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability after Unusually Low Doses of Dasatinib in Chronic Myeloid Leukemia Patients Intolerant to Standard-Dose Dasatinib Therapy

Abstract: We report our experience in 4 patients with chronic myeloid leukemia (CML) who had discontinued imatinib as a result of adverse events and had switched to dasatinib. The chronic phase (n 2) and accelerated phase (n 2) CML patients received dasatinib at starting dose of 100 and 140 mg once daily, respectively. Reappearance of hematological toxicity was observed in 3 patients and pancreatitis in one patient. Treatment was given at a lower dose and patients were followed. The median follow-up was 13 months and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…2013 ; Sprycel ® BMS 2013 ). Early studies showed that cytopenias were usually reversible and effectively managed with dose interruption or reduction, with a minority of cases requiring blood transfusions or hospitalization (Apperley et al 2009 ; Brave et al 2008 ; Cortes et al 2007a , 2008 ; Guilhot et al 2007 ; Hochhaus et al 2007 ; Ottmann et al 2007 ; Quintás-Cardama et al 2009b ; Serpa et al 2010 ; Shah et al 2008a ). In one study, cytopenias resolved in 60 % of patients upon interruption (Talpaz et al 2006 ); in another study, permanent discontinuation was required in only 1 % (Brave et al 2008 ).…”
Section: Clinical Investigations Of Dasatinibmentioning
confidence: 99%
See 1 more Smart Citation
“…2013 ; Sprycel ® BMS 2013 ). Early studies showed that cytopenias were usually reversible and effectively managed with dose interruption or reduction, with a minority of cases requiring blood transfusions or hospitalization (Apperley et al 2009 ; Brave et al 2008 ; Cortes et al 2007a , 2008 ; Guilhot et al 2007 ; Hochhaus et al 2007 ; Ottmann et al 2007 ; Quintás-Cardama et al 2009b ; Serpa et al 2010 ; Shah et al 2008a ). In one study, cytopenias resolved in 60 % of patients upon interruption (Talpaz et al 2006 ); in another study, permanent discontinuation was required in only 1 % (Brave et al 2008 ).…”
Section: Clinical Investigations Of Dasatinibmentioning
confidence: 99%
“…2013 ; Sprycel ® BMS 2013 ). Early reports indicate that most nonhematologic AEs, including neuropathy, dyspnea, elevated liver enzymes, headache, bone pain, rash, renal failure, cardiac abnormality, infections, pancreatitis, and diarrhea, were effectively managed with dose reductions or interruptions (Apperley et al 2009 ; Cortes et al 2008 ; Hochhaus et al 2007 ; Serpa et al 2010 ). Consistent with reports, guidelines indicate that most pleural effusion events can be managed through dose reduction or interruption, and/or corticosteroids and diuretics, with a minority of cases requiring thoracentesis, oxygen therapy, or pleurodesis (Brave et al 2008 ; Cortes et al 2007a , 2008 ; Guilhot et al 2007 ; Hochhaus et al 2007 ; Kantarjian et al 2012 ; Laneuville et al 2011 ; Shah et al 2008a ; Talpaz et al 2006 ).…”
Section: Clinical Investigations Of Dasatinibmentioning
confidence: 99%
“…One study was later excluded because treatment schedules used were not in line with current practice [ 16 ]. During the process of search expansion, four additional studies were included [ 10 , 17 19 ]. In total, 34 studies met eligibility criteria for this review (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CMR in 20% and MMR 22%. Nil Nil Serpa et al (2010) Brazil [ 17 ] To report in 4 cases the safety and efficacy of low doses of dasatinib Case report, sample = 4, indication CML Varied: range 20-140mg od, different durations and interruptions Licensed monotherapy starting dose:100 mg od Responses include CCyR or MMR or both. High grade thrombocytopenia and neutropenia Nil Abbadessa et al (2011) Italy [ 39 ] To report in four cases treated with sorafenib, the efficacy and tolerability of prolonged low dosing Case report, sample = 4, indication: advanced HCC Only case 4 has extractable dose data: 400 mg 10/7, withheld for 1/12, restarted at 50% for 4/12, withheld 9/7, restarted 400 mg e.o.d Licensed monotherapy starting dose:400 mg bd PR after 3 months.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that low doses of dasatinib have been used without compromising its efficacy. 25 Since dasatinib has 100-300-fold activity compared to imatinib, a reduced dose (50 mg per day) could be sufficient for optimal response at cost similar to full-dose imatinib as front-line treatment, making this an attractive option that warrants further investigation.…”
Section: Initial Treatmentmentioning
confidence: 99%